(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The main materials used in producing interlock bricks are clay, sand, and cement as usually applied in the conventional process of making bricks. There is, however, a continuous reduction in the availability of these natural resources due to their non-renewability. Therefore, one of the materials with the ability to support the acoustic and thermal performance of buildings in architecture is plastic. Plastics are categorized as lightweight, non-breakable, non-corrosive, and resistant to weather. Moreover, there is no need for the production of new plastics for this purpose due to the global call for the use of plastic wastes based on their high economic value. Therefore, this research aimed to compile a study on interlock brick innovation using recycled plastic waste to support the acoustic and thermal performance of a building. This was conducted through a review of previous studies on the profile of interlock bricks produced from recycled plastic waste. The findings are expected to provide information on the efficient production of interlock brick innovation using plastic wastes as a component.